On some aspects of marginal cyclones (MAUSAM, 1989)
Very few of the tropical vortices attain the intensity of hurricanes whereas quite a few of them reach up to the stage of marginal cyclones. One of the very important factors quoted often for blocking the intensification of a tropical cyclone is the wind shear of the ambient environment", Only when the tropical vortex comes under the influence of more powerful but favourable factors, does the further intensification take place. Amongst the numerous factors which may lead to intensification of an incipient tropical vortex are the influence of interaction with westerly troughs and increased boundary layer convergence as a result of landfall. This paper describes satellite observed aspects of evolution in strongly sheared environment, role of westerly troughs and temporary intensification of tropical cyclones on approaching a coast. Finally difficulties encountered in the tropical cyclone intensity analysis using INSAT-1B data are highlighted to apprise the readers of limitations  of satellite analysis currently being pursued.